Realigning Academic Cybersecurity Research With Industrial Needs in Cyber-Physical Systems - Anant Kumar Verma; Alex Dario Navas-Fonseca; Claudio Burgos-Mellado; Tomislav Dragicevic (IEEE Open Journal of the Industrial Electronics Society)
The exponential advancements in distributed control and communication architectures have significantly transformed industrial cyber-physical systems (ICPSs). Among the critical enablers of ICPSs, security has emerged as a key focus due to growing concerns about safeguarding industrial assets from both physical and cyber damage. However, security is not the sole enabler of ICPSs; advancements in field instrumentation, sensor technologies, interoperability, and resilient control strategies also play pivotal roles. In recent years, the evolution of wireless embedded devices has particularly modified the operational behavior of critical infrastructures, such as power grids, nuclear plants, oil and gas facilities, water treatment systems, and petrochemical plants. These infrastructures, exemplified by the power grid sector’s heightened awareness after the 2015 Ukraine power grid attacks, face complex challenges in addressing both cyber and physical vulnerabilities. Despite increasing academic and industrial attention, there remains a gap in systematically addressing these challenges across various critical sectors. Therefore, this article presents a comprehensive perspective on ICPSs, fostering collaboration between academia and industry to better prepare against cyber threats and enhance the robustness of critical infrastructures.